The construction and meaning of EasyJet airline 2016 advertisements - Wibowo, Laurensius Nikolas; Laksman-Huntley, Myrna (citeus, 2023)
EasyJet, a UK low-cost airline service provider launched several attractive advertisements to attract consumers' interest, one of which is a series of posters issued in 2016. These posters are interesting because the words show complex morphological processes and implied meanings that can be extracted. Previous studies have mostly examined morphological formation or have conducted semiotic studies, but none have linked morphological processes and images on posters with a semiotic approach. Therefore, this study analyzes the word formation process in the 2016 EasyJet advertisement, which has undergone a derivation process, and finds out the meaning contained in the advertisement using a semiotic approach. This qualitative study examines the posters based on Lehmann and Berthet’s (2018) theory of word formation and Barthes' (2013) semiotics theory. The result of this study indicates that in this advertising poster, EasyJet attracts people to use its services in several market segments or consumer groups according to their respective characteristics. The stratagem revealed through these posters is that EasyJet is an airline that wants to invite its prospective passengers to explore new activities.